An Analysis of Guest Relation Officer Responses to Complaints at Zeus Restaurant, Apsara Beach Front Resort and Villa, Thailand - Musa, Mukhammad; Wijoyo, Tuwuh Adhistyo (Manunggal Halim Jaya, 2025)
This study examines the role of Guest relations officers (GROs) in handling complaints at Zeus Restaurant, Apsara Beach Front Resort and Villa, Thailand, focusing on the effectiveness of various complaint management strategies and their impact on guest satisfaction. Utilizing a qualitative research approach, the study involved semi-structured interviews with 10 GROs to explore common types of complaints, the strategies employed for resolution, and the outcomes of these strategies. Findings revealed that complaints primarily concern services, food quality issues, and staff behaviour. GROs effectively managed these complaints through immediate acknowledgement, empathetic communication, and prompt problem resolution. The study highlighted the significance of follow-up actions, such as checking in with guests and offering compensatory gestures, in enhancing guest satisfaction and loyalty. Thematic analysis of the interview data indicated that well-handled complaints could transform negative experiences into positive ones, thereby improving overall guest perceptions and service quality. The research underscores the importance of training GROs in emotional intelligence and problem-solving skills and suggests that advanced technologies and structured complaint management processes are crucial for maintaining a high standard of service. This study contributes to the understanding of effective complaint-handling practices in luxury hospitality settings and provides insights into enhancing guest relations and operational excellence.